Patient satisfaction levels in dental health care: a case study of people in North Mamuju, Indonesia 2017 - Fuad H. Akbar; Burhanuddin D. Pasiga; Rasmidar Samad; Ikhlas Bakri (Journal of Dentomaxillofacial Science, 2018)
Objective: This research aims to describe the level of patientssatisfaction in dental health services, study of people in North MamujuRegency, West Sulawesi of Indonesia.Material and Methods: Patient satisfaction is a useful measure thatcan be used to evaluate the service quality. Satisfaction is a comparisonbetween the perceptions of services received with expectations, whilethe quality of health services is act or services provided by one party toanother in form of care or provision of health facilities. To improve thequality of a health service that is necessary to do research on the levelof patient satisfaction in dental health care.Results: This research is Pathfinder Method Survey. Descriptiveobservational research with cross-sectional study design, populationof the entire community of District Sarjo and Bambaira, North MamujuWest Sulawesi of Indonesia and research subjects were aged >18years. The study found dimensions of empathy shows that 43 (100%)respondent satisfied while dimensions of assurance most not satisfiedthat 4 (14.0%) respondent.Conclusion: Patient satisfaction is highest in the dimension of empathythen the dimensions of physical appearance, dimensional medicalservices followed responsiveness and the last on assurance dimensions.